2008
DOI: 10.1177/1049731508314265
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Approach to Reducing Runaway Behavior and Stabilizing Placements for Adolescents in Foster Care

Abstract: Teenagers' running from foster placement is a significant problem in the field of child protection. This article describes a functional, behavior analytic approach to reducing running away through assessing the motivations for running, involving the youth in the assessment process, and implementing interventions to enhance the reinforcing value of placements for adolescents, thereby reducing the probability of running and associated unsafe periods. A case study illustrates this approach and a study compares 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 25 publications
3
26
0
3
Order By: Relevance
“…A report by the Chapin Hall Center found that youth who ran away from foster care frequently explained their runaway behavior as attempting to reconnect with family or friends (Courtney et al, 2005). One practice implication for permanency outcomes would be to create interventions and supports that assist youth with being connected in their foster care placements (for example, Clark et al, 2008). Youth development theory suggests that these connections are essential as are opportunities for contribution and participation.…”
Section: Social Work Practicementioning
confidence: 99%
“…A report by the Chapin Hall Center found that youth who ran away from foster care frequently explained their runaway behavior as attempting to reconnect with family or friends (Courtney et al, 2005). One practice implication for permanency outcomes would be to create interventions and supports that assist youth with being connected in their foster care placements (for example, Clark et al, 2008). Youth development theory suggests that these connections are essential as are opportunities for contribution and participation.…”
Section: Social Work Practicementioning
confidence: 99%
“…Efforts to assist older youth in homeless families through tailored support and, where appropriate, reunification efforts may have long‐lasting benefits. Older children and adolescents separated from their biological families are vulnerable relative to their peers in a variety of ways, including greater risks of being homeless on their own (Clark et al., 2008; Courtney & Dworsky, 2006) and other issues that may create challenges for their continued development such as dropout, unplanned pregnancy, and mental health and substance use problems (Courtney & Dworsky, 2006). Addressing these issues at this critical juncture, before youth face adult legal and economic responsibilities and risks, may reduce the likelihood of future generations of homeless families.…”
Section: Recommendations: Addressing the Needs Of Children And Familimentioning
confidence: 99%
“…Previous studies have attempted to predict the factors involved with running away from out‐of‐home care. Recently, Clark and colleagues (), and Courtney and Zinn (), provided a comprehensive summary of research findings regarding significant predictors of running away from out‐of‐home care in the USA. Child age and gender, have been found to be related to running away from out‐of‐home care (Biehal and Wade, ; Courtney and Zinn, ).…”
Section: Introductionmentioning
confidence: 99%